Essentials of : medical pharmacology - Tripathi, KD (New Delhi : Japee Brothers Medical Publishers, 2009)
5.Pharmacology is both a basic and an applied science. It forms the backbone of rational therapeutics. Whereas the medical student and the prescribing physician are primarily concerned with the applied aspects, correct and skilful application of drugs is impossible without a proper understanding of their basic pharmacology. Medical pharmacology, therefore, must include both fundamental back- ground and clinical pharmacological information. Objective and quantitative data on the use of drugs in man, i.e., relationship between plasma concentration and intensity of therapeutic/toxic actions, plasma half lives, relative efficacy of different medications and incidence of adverse effects etc., are being obtained with the aim of optimising drug therapy. The concepts regarding mechanism of action of drugs are changing. In addition, new drugs are being introduced in different countries at an explosive pace. A plethora of information thus appears to be important. However, trying to impart all this to a medical student would be counter-productive. One of the important aims of this book is to delineate the essential information about drugs. The opening sentence in each chapter defines the class of drugs considered. A 'prototype' approach has been followed by describing the representative drug of a class followed by features by which individual members differ from it. Leading trade names have been included. Clinically relevant drug interactions have been mentioned.
Section 1. General Pharmacological Principles Section 2. Acting on Autonomic Nervous System Autonomic Nervous System: General Section 3. Autacoids and Related Drugs Section 4. Respiratory System Drugs Section 5 Hormones and Related Drugs and other
Texto en Inglés Index
Keywords: FARMACOLOGÍA; FARMACOLOGIA CLINICA